PERAN CORE VALUE “AKHLAK” DALAM MENINGKATKAN KINERJA KARYAWAN PT KAI (PERSERO) DAOP 4 SEMARANG - Ahmad Nur Kalinggar; Febrianur Ibnu Fitroh Sukono Putra; Artha Febriana; Elia Resha Fatmawati (Politeknik Negeri Ambon, 2026)
Introductions: When faced with challenges in the transportation industry and the high demands of public services, PT KAI (Persero) applies the core values of